Correlation Between the Koebner Phenomenon and Clinical Features in Vitiligo - Tang X; Hao C; Fan M; Dong P; Qi Y; Gao J; Huang H; Chen M; Wang W (Clinical, Cosmetic and Investigational Dermatology)
Xianfa Tang,1– 3,* Cuilan Hao,1– 3,* Min Fan,1– 3,* Penghao Dong,1– 3 Yinyin Qi,1– 3 Jinping Gao,1– 3 He Huang,1– 3 Mengyun Chen,1– 3 Wenjun Wang1– 3 1Department of Dermatology, The First Affiliated Hospital of Anhui Medical University, Hefei, Anhui, People’s Republic of China; 2Institute of Dermatology, Anhui Medical University, Hefei, Anhui, People’s Republic of China; 3Key Laboratory of Dermatology (Anhui Medical University), Ministry of Education, Hefei, Anhui, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wenjun Wang, Email wangwj0720@sina.comPurpose: To investigate the correlation between the presence of the Koebner phenomenon (KP) and clinical features of patients with vitiligo.Patients and Methods: The clinical characteristic data, including age, age of onset, disease duration, gender, clinical stage, clinical type, family history, and comorbid immune-related diseases, of 1472 patients with/without KP were analyzed with SPSS 17.0 software.Results: Of the 1472 patients, 290 (19.70%) were positive for KP. The clinical course (6.95 vs 5.62, P = 0.015), percentage of patients with progressive stage (78.97% vs 70.05%, P = 0.002), the acrofacial type (4.49% vs 1.69%, P = 0.004), comorbid immune-related diseases (28.29% vs 19.04%, P = 0.001) and lesion area ≥ 2% (47.24% vs 38.24%, P = 0.005) in KP-positive group were significantly greater than those in KP-negative group. Binary logistic regression analysis found that progressive stage (P = 0.003, OR = 1.60, 95% confidence interval (CI): 1.17– 2.18), area of skin lesion ≥ 2% (P = 0.008, OR = 1.44, 95% CI: 1.10– 1.88) and comorbid immune-related diseases (P = 0.001, OR = 1.63, 95% CI: 1.21– 2.20) were significantly associated with KP.Conclusion: The presence of KP in patients with vitiligo is associated with clinical progression, the acrofacial type, comorbid immune-related disease and a larger lesion area. This study suggested the presence of KP may be an indicator of disease activity and aggression, and underlay its importance in the management of disease.Keywords: vitiligo, Koebner phenomenon, clinical features